Is early defoliation a sustainable management practice for mediterranean vineyards? case studies at the portuguese Lisbon winegrowing region - Lopes, C.M. (2019)
Context and purpose of the study - Recently early defoliation (ED) has been tested in several highyielding grapevine varieties and sites aiming at reducing cluster compactness and hence, regulating yield and susceptibility to botrytis bunch rot infection. The reported results have been generally positive, encouraging growers to use this canopy management technique as an alternative for replacing the conventional time-consuming cluster thinning and, simultaneously, as a sustainable practice to reduce the use of fungicides. However, ED increases berry sunburn risks and/or can induce carry-over effects on vigor and node fruitfulness as shown in the two case studies reported in this work. Material and methods- Two ED experiments were set up at a commercial vineyard located in the Lisbon winegrowing region with the varieties Aragonez, syn. Tempranillo (2013-2015) and Semillon (2018). In both experiments the ED treatment was compared with the non-defoliated (ND; control) using a randomized complete block design with 4 replicates per treatment. The ED treatment consisted of the removal of 5-6 basal leaves and any laterals at pre-flowering. Vegetative (leaf area and pruning weight) and reproductive components (%fruit-set, cluster number, cluster weight, yield) and berry composition were assessed